2015
DOI: 10.1111/eip.12295
|View full text |Cite
|
Sign up to set email alerts
|

Clinical symptoms predict concurrent social and global functioning in an early psychosis sample

Abstract: Clinical domains such as negative symptoms and social interaction anxiety significantly contribute to an optimal model predicting outcome during the early phase of a psychotic disorder. These clinical features may also provide useful markers of an individual's capacity for social participation. Clinical implications include the need for early targeted intervention to address social anxiety and negative psychotic symptoms to facilitate optimum patient outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
5
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 64 publications
(99 reference statements)
4
5
0
1
Order By: Relevance
“…Higher NS at baseline were associated with worse functioning at 1-year follow-up as reflected by the GAF-d scores. This finding is consistent with most FEP studies to date that show NS as a critical determinant of both global and social functioning (Cacciotti-Saija et al, 2015) and real-world functioning (Robertson et al, 2014), for at least 2 years after the FEP (Bergé et al, 2016). Recent research also supports this link in individuals at clinical risk of psychosis (Meyer et al, 2014).…”
Section: Negative Symptoms: Clinical and Functional Outcomessupporting
confidence: 89%
“…Higher NS at baseline were associated with worse functioning at 1-year follow-up as reflected by the GAF-d scores. This finding is consistent with most FEP studies to date that show NS as a critical determinant of both global and social functioning (Cacciotti-Saija et al, 2015) and real-world functioning (Robertson et al, 2014), for at least 2 years after the FEP (Bergé et al, 2016). Recent research also supports this link in individuals at clinical risk of psychosis (Meyer et al, 2014).…”
Section: Negative Symptoms: Clinical and Functional Outcomessupporting
confidence: 89%
“…The disorder is often described in terms of positive symptoms, such as hallucinations and delusions, and negative symptoms, such as reduced emotional expression and lack of motivation (Bozikas and Andreou, 2011 ). In addition, recent researches have suggested that working memory dysfunction may be a core component of schizophrenia (Lee and Park, 2005 ; Vu et al, 2013 ; Cacciotti-Saija et al, 2015 ; Jiang et al, 2015 ; Mourik et al, 2015 ; Schwarz et al, 2016 ), and that such dysfunction may be the result of abnormal activity in a specific brain network (Glahn et al, 2005 ; Minzenberg et al, 2009 ; Jiang and Zhou, 2012 ) involving the dorsolateral prefrontal cortex (DLPFC) (Goldman-Rakic, 1999 ). However, results regarding the contribution of this region remain inconsistent.…”
Section: Introductionmentioning
confidence: 99%
“…Patients from groups B and C displayed high levels of negative symptoms at baseline, though these symptoms remain high only in group C. This may be linked to a different illness profile and neurobiological basis between groups B and C, which is actually in line with our results showing that they have distinct metabolic profiles. Group C may consist of patients with persistent trait-related negative symptoms, known indicators of poor psychosocial outcome [51][52][53]. The GPx activity was particularly high in group C, suggesting that they may benefit from antioxidant add-on therapy [35] such N-acetyl-cysteine, which improves negative symptoms [54,55].…”
Section: Discussionmentioning
confidence: 99%